How Does the Value Stream Mapping Method Identify Waste and Improve the Coffee Bean Production Process of a Café? - Febriana Wurjaningrum; Caraka Abi Abdilah Shafak (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2022)
Objective: This study aims to identify waste and its causes in the production process and provide suggestions for improvement. Design/Methods/Approach: The author uses a qualitative research method approach to obtain research data. The author identifies the waste that occurs using Value Stream Mapping (VSM). Identify waste in the coffee bean production process using structured question weighting and direct interviews with several parties related to the production process, including the café owner, production manager, head barista, and two baristas in the production section. Findings: The waste causes that occur in the identified coffee production process are waiting time due to the first stage sorting process still using hands manually, the absence of tools, defects caused by the inevitable side effects of the roasting process, and unnecessary motion. After knowing the cause of the waste that occurred, the company was given a suggestion for improvement using 5W-1H tools, such as using a coffee sieve of a certain size for the first stage sorting process, making a new product in the form of ground coffee, processing defect coffee beans that always exist from the roasting results, and adding a fan and exhaust in the roasting room to reduce unnecessary movement during the process. Originality: The paper contributes to the limited literature on lean production in the coffee processing business and disseminates this information to improve production efficiency.